Cropland / pastureland dynamics and the slowdown of deforestation in Latin America - Grasser, J (2015)
Latin America has the planet?s largest land reserves for agriculture and had the most rapid agriculturalexpansion during the twenty-first century. A large portion of the expansion replaced forests, as shownby many local and regional studies. However, expansion varied regionally and also replaced other landcovers. Further, it is important to distinguish between changes in cropland and pastureland as theyproduce food at different levels of efficiency and intensity.Weused thirteen years (2001?2013) ofMODerate Resolution Imaging Spectroradiometer satellite imagery to characterize cropland andpastureland expansion at multiple scales across Latin America. From 2001 to 2013, 17% of newcropland and 57% of new pastureland replaced forests throughout Latin America. Croplandexpansion from 2001 to 2013 was less (44.27 Mha) than pastureland (96.9 Mha), but 44% of the 2013cropland total was new cropland, versus 27% of the 2013 pastureland total, revealing higher regionalexpansion rates of row crop agriculture. The majority of cropland expansion was into pasturelandwithin core agricultural regions of Argentina, Brazil, Bolivia, Paraguay, and Uruguay. Onthe contrary,pastureland largely expanded at frontiers, such as central Brazil, western Paraguay, and northernGuatemala. As others have suggested, regional agriculture is strongly influenced by globalization.Indeed, we find an overall decrease in agricultural expansion after 2007, coinciding with the globaleconomic slowdown. The results illustrate agricultural cropland and pastureland expansion acrossLatin America is largely segregated, and emphasize the importance of distinguishing between the twoagricultural systems, as they vary in land use intensity and efficiency.